2008
DOI: 10.1111/j.1365-3083.2007.02059.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Properties of the Antibody Response to Plasmodium vivax Duffy Binding Protein in an Area with Unstable Malaria Transmission

Abstract: The function of the Plasmodium vivax Duffy binding protein (DBP) during the erythrocyte invasion process is critical for successful parasite growth and pathogenesis in human infections. Although DBP is the subject of intensive malaria vaccine research, investigations on the functional proprieties of anti‐DBP antibodies in the human population have been limited [Infect Immun68 (2000) 3164]. In the present study, we examined the ability of sera from different populations of the Brazilian Amazon – an area of mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 31 publications
3
46
1
3
Order By: Relevance
“…At 24 h after transfection, the efficiency of transfection was assessed by fluorescence; the recombinant protein expression levels were similar between the Sal-1 and outbreak DBPII variants (data not shown). Forty-eight hours after transfection, the erythrocyte-binding assays were performed as described previously [21]. For this, anti-serum was added at 1 : 20 (1 h at 37°C, 5% CO2) followed by incubation with 10% of human O + erythrocytes suspension (2 h, room temperature).…”
Section: Cos Cell Transfection and Erythrocyte-binding Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…At 24 h after transfection, the efficiency of transfection was assessed by fluorescence; the recombinant protein expression levels were similar between the Sal-1 and outbreak DBPII variants (data not shown). Forty-eight hours after transfection, the erythrocyte-binding assays were performed as described previously [21]. For this, anti-serum was added at 1 : 20 (1 h at 37°C, 5% CO2) followed by incubation with 10% of human O + erythrocytes suspension (2 h, room temperature).…”
Section: Cos Cell Transfection and Erythrocyte-binding Assaysmentioning
confidence: 99%
“…Currently, available data on humoral immune responses to DBP in human populations demonstrate that anti-DBP antibodies increase with exposure to P. vivax [17][18][19][20], and this immune response includes antibody activity that blocks adherence of DBPII to its receptor on erythrocytes [18,21]. The same antibodies that block the DBPII-DARC interaction also inhibit P. vivax erythrocyte invasion [22], which is proof-of-concept that anti-PvDBP antibodies can inhibit merozoite invasion.…”
Section: Introductionmentioning
confidence: 96%
“…Similar to other plasmodial proteins known to participate in such processes, PvDBP is suggested to be an important vaccine candidate antigen, because it elicits strong immune responses in humans [5,6]. Experimental evidences that antibodies against PvDBP inhibit the interaction of this protein with DARC in vitro and block the invasion of P. vivax into human erythrocytes also support the notion that this protein is a potential asexual blood stage vaccine candidate antigen against P. vivax [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…Antibody responses to PvDBP have been shown in endemic populations of P. vivax infection in Papua New Guinea, [23][24][25] Brazil, [26][27][28] and Colombia. 29 In addition, different studies suggested that stronger humoral and cellular immune responses to PvDBP-II develop progressively with increasing age, 22,24,29,30 showing a boosting effect that was likely because of repeated exposures to the infection.…”
Section: Introductionmentioning
confidence: 99%